Experimental investigation of wind effects on long-span slender bridges with stochastic traffic flow - Nelson, Ryan Scott, author; Chen, Suren, 1973-, advisor; Bienkiewicz, Bogusz, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2011)
The aeroelastic and aerodynamic effects on long-span slender bridges due to traffic has traditionally been neglected as it is assumed that the bridges will be closed to traffic under strong winds. However, with ever changing weather, natural disasters, and important roles of many long-span bridges throughout the United States, the reality is that these long-span bridges are often not closed and there are still many vehicles on the bridges even when considerably strong winds exist. Therefore, to rationally evaluate the aerodynamic performance of a bridge deck, the impacts from stochastic traffic should be appropriately considered as a key part toward any safety or serviceability study. The present study discusses the wind tunnel experimental tests of a long-span bridge section with stochastic traffic. The details of the experimental investigations are reported, including the design and construction of a bridge section model, two-degree-of-freedom testing frame and vehicle models representing stochastic traffic. Several tests were performed to determine a baseline for the bridge section without traffic, under different wind speeds and attack angles. The bridge section was then re-tested with many scenarios representing stochastic and extreme traffic conditions. The aeroelastic flutter derivative coefficients were extracted using the iterative mean square method and the values plotted and compared with the baseline results. Under the given reduced velocity range being tested, it is observed that several traffic scenarios increase the aeroelastic and aerodynamic effects as the bridge section becomes more susceptible to flutter and vortex shedding. Finally, the statistical descriptions of the flutter derivatives with the presence of traffic on the bridge section model are also made.
Keywords: aeroelastic; wind effects; traffic; flutter derivatives; bridges